Analisis Pengembangan Electronik Government pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Palangka Raya - Praja Panjika, Yunus (Journal Ilmu Sosial, Politik dan Pemerintahan, 2022)
The concept of Electronic Government Development which is examined by researchers aims to describe how the development of Information Technology in the Office of Investment and One Stop Integrated Services of Palangka Raya City is in accordance with the Concept of Elements of Success in Electronic Government Jhon F Kennedy School of Government. Based on the results of research conducted by researchers on the development of Electronic Government carried out by the Office of Investment and One Stop Services in Palangka Raya, it is in accordance with the concept of Implementation of Electronic Government Development in Indonesia, according to Nugroho. This can be seen from the Development of Electronic Government Applications carried out by the Investment and One Stop Service Office of Palangka Raya City where the Electronic Government Development is already at the web presence and interaction stage, namely the facilities provided on the website contain content for information facilities and the online public complaint service complaint service process but have not yet reached the Transaction and Transformation stage, namely the website facilities developed can provide online licensing services and websites can be integrated directly between Government Agencies. After an analysis by researchers using the Concept of Elements of Success in Electronic Government John F Kennedy School of Government has found the factors that influence the development of technology in the concept of Electronic Government at the Office of Investment and One-Stop Integrated Services, Palangka Raya City, namely the limited Human Resources. who can carry out technology development and the limited budget in technology development and the absence of related socialization related to web-based information services provided by the Palangka Raya City Investment and One Stop Integrated Service Office